2014
DOI: 10.2147/ceg.s43084
|View full text |Cite
|
Sign up to set email alerts
|

Advances, problems, and complications of polypectomy

Abstract: The major role of colonoscopy with polypectomy in reducing the incidence of and mortality from colorectal cancer has been firmly established. Yet there is cause to be uneasy. One of the most striking recent findings is that there is an alarmingly high incomplete polyp removal rate. This phenomenon, together with missed polyps during screening colonoscopy, is thought to be responsible for the majority of interval cancers. Knowledge of serrated polyps needs to broaden as well, since they are quite often missed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 117 publications
0
20
0
Order By: Relevance
“…The most common complications are perforation and hemorrhage [12,13]. Most of the serious complications have been reported to occur not during diagnostic interventions but during therapeutic procedures such as polypectomy and dilatation [14].…”
Section: Introductionmentioning
confidence: 99%
“…The most common complications are perforation and hemorrhage [12,13]. Most of the serious complications have been reported to occur not during diagnostic interventions but during therapeutic procedures such as polypectomy and dilatation [14].…”
Section: Introductionmentioning
confidence: 99%
“…There are some disadvantages of SFP technique such as low one-bite polypectomy and complete resection rates, and increased risk of residual tissue. 4 , 10 , 12 One of the reasons might be inadequate examination of polypectomy area because of bleeding after the first bite. 4 In our study, complete resection rate was high in the SFP group when compared with the literature.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 10 , 12 One of the reasons might be inadequate examination of polypectomy area because of bleeding after the first bite. 4 In our study, complete resection rate was high in the SFP group when compared with the literature. However, it indicated that more bites were required to obtain this resection rate (Figure 2 A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that recurrence of advanced adenoma was associated with the size of primary polyps (>1 cm) and their location in the colon. However, the mechanism associated with polyp recurrence has not been clarified [ 13 , 14 ]. It is possible that underlying impairment could exist in normal-appearing colon mucosa in colon polyp patients; therefore, recurrent polyps may appear after complete removal of the original colon polyp.…”
Section: Introductionmentioning
confidence: 99%